Intervención en suelo de expansión urbana enfocado en la reubicación del asentamiento villa del rio en el área urbana de Tello-Huila (2022)
The case of the informal settlement Villa del Río, in the north of the urban area of the municipality of Tello, Huila, is exposed. To frame and contextualize the problem, an analysis and diagnosis is carried out, at different scales, based on a methodology proposal according to the population to be investigated and endless data and necessary references, which seeks to carry out a project according to the social dynamics and urban of that place, starting with a basic research question, which will be answered through a sectoral urban design proposal of the